Lipid-based nanoparticles as drug delivery carriers for cancer therapy - Waheed, Ibtesam; Ali, Anwar; Tabassum, Huma; Khatoon, Narjis; Lai, Wing-Fu; Zhou, Xin (Frontiers in Oncology, 2024)
Cancer is a severe disease which results in death in all countries of the world. Nano-based drug delivery approach is the best alternative, directly targeting cancer tumor cells with improved drug cellular uptake. Different types of nanoparticle-based drug carriers are advanced for the treatment of cancer and to increase the therapeutic effectiveness and safety of cancer therapy, many substances have been looked into as drug carriers. Lipid-based nanoparticles (LBNPs) have significantly attracted interest recently. These natural biomolecules that alternate to other polymers frequently recycled in medicine constructions due to their amphipathic property. Lipid nanoparticles typically provide a variety of benefits with biocompatibility and biodegradability. This review covers different classes of LBNPs, including their characterization and different synthesis technologies. The most significant advancements in lipid nanoparticle technology and their use in medicine administration. Moreover, the review also emphasized the applications of lipid nanoparticles that are used in different cancer treatment types.